(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses the legal regulation of the legislative initiative right of the President of Kazakhstan, forms and procedures for its implementation. The article also presents issues of the draft legislation introduced by the President of the Parliament RK, as well as the procedure for its application.